Casamento e AIDS: um olhar teológico sobre a contaminação feminina na região sul da Bahia - Gonçalves, Maria Vitória Ramos (2012)
Marriage is part the seven sacraments in Catholic theology and is a representation of the union between Christ and the Church. The couple that is joined in marriage vows in front of a community to establish an indissoluble bond ruled in love and faithfulness. So, it is expected that man and woman who marry build a home where children learn important moral and religious values. There is, however, that the home has is not been the environment protection that should be and this space is that many women who have only one sexual partner have been infected with VIH/AIDS. Numerous surveys in the country have shown feminization syndrome and placed married women in this risk group. Given these considerations, this research aimed to investigate whether the city of Itabuna the married women are also the ones that have been more contaminated. In addition, we attempted to raise the socioeconomic profile of these women and how they deal with the certainty of infection. There was also a silencing by the Catholic Church in this matter, as it occurs in other Brazilian states.